Structural characteristics of two heavy hail supercell storms forced by low-level warm advection - Jia TANG; Kun ZHANG; Minghui TANG; Hui ZHOU; Mei HU (暴雨灾害, 2023)
There were two rare 6 cm hailstones under the background of low-level warm advection forcing in Huaihua of Hunan Province on March 21 and May 4, 2020. Based on the meteorological stational data and the Doppler weather radar data, the structures of intensity and dynamic fields of the supercell storms for these two events are analyzed. Results are showed below. (1) Both cases occur under the background of low-level warm advection forcing. Moderate-intensity convective effective potential energy, large deep vertical wind shear, and high energy helicity favored the organizational development and maintenance of storms, and the ground convergence line is the main trigger factor of severe convection weather. (2) The 6-cm hails in the two cases both occurred in the early mature stage of supercell storm, which are caused by the "supercell-like" storm without the characteristics of mesocyclone, but with the characteristics of hook echoes, sidelobe echoes, three-body scattering spike, and echo overhangs. (3) In the intense development stage, the vertical dynamic fields of the storms are both featured by the structure of low-level convergence, the double-vortex-tube rotating structure of cyclonic rotation and anticyclonic rotation in the middle level (referred to as double vortex) and high-level divergence. (4) The maximum reflectivity and the cells-vertical integrated liquid both reach 67 dBz and 69 kg·m-2.The decrease of height top and the strongest-shear height reflect hail falling.